H-RAS 81 polymorphism is significantly associated with aneuploidy in follicular tumors of the thyroid - Castro, P; Soares, P; Gusmão, L; Seruca, R; Sobrinho-Simões, M (Oncogene, 2006)
Follicular thyroid tumors are often aneuploid. It was advanced that chromosomal instability is closely associated to RAS mutations, but such association remains unproven. H- RAS can be alternatively spliced in two different proteins, p21 and p19, the former being the active protein. In order to investigate the relationship between RAS mutational status and ploidy in thyroid tumors, we analysed RAS genes in a series of 99 follicular lesions (14 nodular goiters, 70 follicular adenomas and 15 follicular carcinomas), eight thyroid carcinoma cell lines and a control group of 102 blood donors, correlating the presence of RAS mutations with the ploidy of the tumors and evaluating the two spliced forms of H- RAS . Overall, 20% of the follicular tumors harbored RAS mutations and 62% of the patients with follicular tumors (and 51% of blood donors) harbored the H- RAS 81T → C polymorphism. The presence of RAS mutations was not associated with aneuploidy. The H- RAS polymorphism did not seem to confer a higher propensity for neoplastic transformation as it was also found in hyperplastic lesions, but was strongly associated with aneuploidy ( P <0.0001). The presence of the H- RAS 81T → C polymorphism was associated with significantly higher amounts of total H- RAS mRNA expression, higher amounts of p21 isoform and a higher fraction of neoplastic cells in S phase. Our results suggest that the H- RAS 81T → C polymorphism may induce aneuploidy through overexpression of the active p21 isoform of H-RAS.